TOTAL FLAVONOIDS CONTENT OF SOME SEASONAL FRUITS AND THEIR BENEFICIAL EFFECTS ON CARDIOVASCULAR DISEASE: A CROSS-SECTIONAL STUDY - NAQVI, SARA; IMAM, SHAHLLA; ALI, FATIMA RAMZAN; AZHAR, IQBAL; ALAM MAHMOOD, ZAFAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study was intended to assess the qualitative and quantitative analysis of some fruits available in Karachi, Pakistan. The association between the intakes of flavonoids enriches fruit and cardiovascular (CV) health was evaluated through a clinical survey. Methods: The acid-alkaline test was executed in all fruit samples. The total flavonoids content was carried out using aluminum chloride calorimetric method. A cross-sectional survey was executed from July to December 2018 among 100 cardiac patients in Karachi, Pakistan. The patient’s blood pressure was determined and categorized into normal, prehypertension, and hypertension. Descriptive statistics and Pearson’s Chi-squared test were executed to demonstrate the participants’ sociodemographic information. Results: The result revealed that the purple grapes contained an abundant amount of total flavonoid contents 192.59±1.28 as compared to green grapes and other fruits, whereas Citrus paradisi (grapefruit), Citrus reticulata (kinnow), and Punica granatum (pomegranate) contained 162.96±0.640, 151.85± 0.640, and 107.03±1.28, respectively. Moreover, Malus species, grapes (green), raspberry, and strawberry are also a good source of flavonoids. The clinical survey revealed that the majority of the respondents were male 74% while only 26% were female. The response rate was 73%. Conclusion: The finding of the present study indicated that dietary intake of fruits containing flavonoids may decrease the risk of CV disease and could contribute to promoting cardiac health.